“Gestión de inventarios para la toma de decisiones gerenciales aplicado a la compañía ICEV&V CIA. Ltda., La Maná provincia de Cotopaxi, año 2020” - Puente Gallo, Alexandra Elizabeth (2021)
Inventory is, in general, the largest asset in the balance sheets and inventory expenses, called cost of goods sold, are usually the largest expense in the income statement, so it is important to Evaluate the efficiency and effectiveness of the System of Internal control of inventories, and the use of financial, material and human resources existing in this area of the companies. The research aimed to develop an inventory management model to improve decision-making for the company ICEV&V CIA. LTDA of the canton La Maná. in 2021 to achieve efficiency, evaluate and optimize the mechanisms of inventory management in the company. The methodology used in the research was a documentary, bibliographic, field, and exploratory, it was essential to start from bibliographic research when dealing with topics such as ours that required the use of many sources such as books, articles, theses, among others, field research was conducted, and finally, we had an exploratory study that focused on gathering specific information through techniques such as surveys and interviews that applied to the company and these results analyzed quantitatively. The result obtained was to identify the problems and risks faced by the company based on the situational diagnosis according to the legal regulations in force, taking into account the policies and regulations that govern the company. The contribution obtained was to detect the shortcomings and serve as a guide through the design of an inventory manual adapted to the company for the storage and proper management, obtaining effective and timely help in achieving its business objectives and management decision making. It is concluded that the inventory management model contributed to the company ICEV&V CIA. LTDA. using effective solutions to improve inventory control and management decision making, thus improving the service to its customers and society in general, providing them with control methods in the activities performed, thus improving the daily work to make it more effective and efficient.